Die Gruppe des Stenus (Hemistenus) hopffgarteni Eppelsheim, 1879 (Coleoptera: Staphylinidae) - Puthz, Volker (Acta entomologica slovenica (Ljubljana), 2003)
The group of Stenus (Hemistenus) hopffgarteni Eppelsheim is revised with special treatment of the S. hopffgarteni-complex. Two new species are described from the Balkans: S. apfelbecki sp. n. from Croatia, Bosnia and Hercegovina, Montenegro, Macedonia, and S. pentheri sp. n. from Bosnia and Hercegovina, Serbia. S. likovskyi Hromádka, 1979 is synonymized with S. hopffgarteni Eppelsheim, 1879. The genitalia are described and distributional data given including the first record of the group from Greece.
Keywords: Coleoptera; entomologija; hrošči; taksonomija